1997
DOI: 10.1038/sj.ejcn.1600421
|View full text |Cite
|
Sign up to set email alerts
|

Selenium status of a group of Scottish adults

Abstract: Objective: To examine dietary selenium intake and indices of selenium status (plasma and red blood cell selenium and glutathione peroxidase activities) in apparently healthy Scottish individuals. Design and subjects: One hundred subjects, aged between 40 and 60 y, completed a seven day weighed food intake and provided blood samples for selenium status analysis. Setting: Inverurie, Aberdeenshire, Scotland. Results: Average reported selenium intake was low (43 mg/d). A signi®cant number of subjects had reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…a mean level of 60 mcg/L was found in a recent Scottish study. 19 Baum showed that low plasma Se is a significantly greater risk factor for mortality than low helper T-cell count, by a factor of 16, and confers a much more significant risk than deficiency of any other nutrient investigated. In HIV-infected children, low levels of plasma Se were significantly and independently related to mortality (RR 5.96, 95%CI 1.32-26.81; P = 0.02) and faster disease progression.…”
Section: Viral Infectionmentioning
confidence: 99%
“…a mean level of 60 mcg/L was found in a recent Scottish study. 19 Baum showed that low plasma Se is a significantly greater risk factor for mortality than low helper T-cell count, by a factor of 16, and confers a much more significant risk than deficiency of any other nutrient investigated. In HIV-infected children, low levels of plasma Se were significantly and independently related to mortality (RR 5.96, 95%CI 1.32-26.81; P = 0.02) and faster disease progression.…”
Section: Viral Infectionmentioning
confidence: 99%
“…Se deficiency is defined by Baum et al (1997) as a plasma level <85(0.g/l, a level not attained in many northern European countries (see p. 210), e.g. a mean level of 60 |xg/l was found in a Scottish study (Shortt et al 1997). Baum et al (1997) showed that low plasma Se was significantly associated with mortality (relative risk 10-8, P < 0002), and conferred a much more significant risk than a low helper T-cell count or deficiency of any other nutrient investigated.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…In plasma only a small amount of Se is incorporated into GSH-Px. Nevertheless, some authors [4] found a positive and significant correlation (r = 0.29; p ! 0.05) between plasma Se and plasma GSH-Px of healthy subjects.…”
mentioning
confidence: 99%